Peran Majelis Shalawat Dhiyaul Hady Dalam Meningkatkan Religiusitas Pada Remaja Kota Tanjung Balai - Ningsih, Windy Apriani; Nasution, Hasan Bakti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In various fields, teenagers are the main focus of society. The role of teenagers in forming good character, instilling noble values, and fostering a sense of love for the country is very important. In Tanjungbalai, an interesting phenomenon emerged where many teenagers enthusiastically took part in the Dhiyaul Hady Shalawat Assembly. The uniqueness of this assembly lies in its members, all of whom come from young people, from guides, vocalists, to hadroh players. Before this assembly was established, the condition of the people of Tanjungbalai was quite worrying. Many teenagers fall into negative activities such as nightlife, hanging out without a clear purpose, and drug abuse. The spirit of love for the Prophet was felt to be lacking among the people. Therefore, Ustadz Encev Fariduddin founded the Dhiyaul Hady Shalawat Council. Qualitative research with descriptive-analytic data analysis methods was used to understand the impact of this assembly. Data was obtained through interviews, observation and documentation, then analyzed using a Sufism approach. The research results showed positive changes in the personalities of teenagers who attended the assembly. The congregation feels an increase in religiosity after joining. The Dhiyaul Hady Council consistently and gradually seeks to develop the spiritual life of teenagers in a way that is interesting and suits their tastes. Commitment, motivation, spirit of brotherhood, and regular dhikr, as well as prayers to Allah SWT. be an important part of this development. Apart from spiritual formation, this assembly also encourages and supports teenagers to strengthen their love for Rasulullah SAW and build relationships with ulama and habaib.